Islamic Leadership Competencies from Abdullah Ad Dumaiji's Perspective - Izzuddin Hamas; Endin Mujahidin; Abas Mansur Tamam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research discusses the competence of Islamic Leadership adapted from the thoughts of Shaykh Abdullah Ad Dumaiji in the book al-imamatul udzma 'inda Ahlu as-Sunnah wal Jamaah or translated Imamah Uzhma Islamic Leadership Concept. This research uses descriptive qualitative research methods, this research is also library research. In other words, researchers look for books, writings, or documents related to the theme then researcher organize them into a topic of discussion with analysis. Shaykh Abdullah Ad-Dumaiji said that there are at least eleven requirements to become an imam. They are Islam, puberty, reason, independence, male, knowledge, justice, self-sufficiency, physical prowess, not ambitious for the Imamate, and descent from the Quraish. He explained his inclination towards the view that the one who is more capable of realizing the objectives of the Imamate is the one who is more entitled to be appointed as Imam, whether he is the best or not the best. For if he is personally pious but weak in management then his weakness will affect the ummah as a whole. On the other hand, if he is strong in politics and can manage all issues well, but he is negligent in obedience, then the impact of his negligence is entirely his personal responsibility, the ummah does not bear it. Of course, the best is the one who has the ability and has a good example in practicing religion.